Antihyperlipidemic and cardioprotective effects of n-hexane extract of Terminalia catappa nuts in hyperlipidaemic and hyperglycemic Wister rats - Batubo, Nimisoere P.; Reuben, Edith; Opusunju, Boma H.; Ogbu, Ojeka Sunday; Victor, Dapper Datonye (International Journal of Research in Medical Sciences, 2025)
Background: Dyslipidaemia and diabetes mellitus are significant risk factors for cardiometabolic disease. This study evaluates the lipid-lowering and cardioprotective effects of the n-hexane extract of Terminalia catappa nuts (TCN) in hyperlipidaemic and hyperglycaemic Wistar rats. Methods: Wistar rats were divided into two groups: negative control and induced groups. The induced group was further subdivided into positive control, standard drug-treated, and TCN-treated groups with 200, 400, and 800 mg/kg/day for six weeks. Serum lipid profiles were assessed using standard biochemical methods after 42 days of treatment with TCN. Data were analysed using one-way ANOVA followed by Tukey’s post-hoc test for multiple comparisons, with significance set at p<0.05. Results: The untreated positive control group exhibited significant elevations in total cholesterol (TC), triglycerides (TG), and low-density lipoprotein (LDL) levels, alongside reductions in high-density lipoprotein (HDL) levels (p<0.05). Treatment with TCN at 400 mg/kg and 800 mg/kg significantly improved lipid profiles, with reductions in TC, TG, and LDL (p<0.001) and an increase in HDL (p<0.001) compared to the positive control group. At 800 mg/kg, the most substantial improvements were observed. Similarly, TCN treatment significantly reduced atherogenic indices, including the atherogenic index of plasma (AIP), atherogenic coefficient (AC), and Castelli risk indices I (CRI-I) and II (CRI-II). Improvements were dose-dependent, with the greatest reductions at 400 mg/kg and 800 mg/kg doses (p<0.001). Conclusions: Terminalia catappa nuts demonstrates significant lipid-lowering and cardioprotective effects in hyperlipidaemic and hyperglycaemic conditions, supporting its potential as a natural therapeutic for managing cardiovascular risks and metabolic syndrome.